Detection of the Helicobacter pylori infection among Coronavirus patients in Wasit province - Mohammed Ibrahim Mohammed (Genius Journals, 2022)
Helicobacter pylori (H.pylori) is normal flora in the stomach, it is opportunistic bacteria that can cause an infection for the stomach may be lead to diseases such as gastritis. About two-thirds of the world’s population is H.pylori infection, where it is more common in developing countries and over (80%) of infected individuals are asymptomatic .some of recent studies highlight on there are correction between H.pylori infection and Gastrointestinal Symptoms in COVID-19 patients This study was aimed to Prevalence of Helicobacter pylori infection among COVID-19 patients in Wasit province. This study was conducted on 120 patients with COVID-19 Infection and gastrointestinal symptoms, their age 22 to 65 years, in period extended from September 2021 to June 2022 in Zahra Hospital; AL- Karma teaching Hospital and COVID-19 Isolation center. The stool and blood samples of COVID -19 Infection have been collected, Non-invasive test (SAT and Cag-IgG) were evaluated in all patients, CTK.biotech and Assure® H. pylori IgG Rapid tests were used and the result confirmed by PCR
Keywords: Helicobacter; gastrointestinal symptoms